Prevention education, neuropathy screening and foot vasculopathy screening in patients with type 2 diabetes mellitus at Medan Area community health centre - Rusdiana, Rusdiana (Talenta Publisher Universitas Sumatera Utara, 2025)
Screening of diabetic foot neuropathy and vasculopathy using monofilament and Ankle-Brachial Index (ABI) devices is a crucial step in the early detection of potential complications in diabetic patients. These screening tools are simple yet effective methods to assess sensory loss and peripheral arterial disease, which are major risk factors for the development of diabetic foot ulcers. Early identification allows for timely interventions that can significantly reduce the risk of severe complications such as infections, gangrene, and lower limb amputations. In addition to regular screening, prevention strategies should be implemented consistently. These include maintaining good glycemic control through routine blood sugar monitoring, adhering to a balanced and regulated diet, and engaging in regular physical activity. One recommended form of exercise is diabetic foot exercise, which helps improve blood circulation in the lower limbs and enhances nerve function, thereby reducing the risk of foot-related complications. Comprehensive foot care education, combined with these preventive measures, plays a vital role in improving the quality of life of individuals with diabetes and minimizing the burden of diabetic foot disease on both patients and the healthcare system.